(untitled) (Superficies y Vacío, 2012)
In this work we report the sensing properties of undoped and ruthenium-doped tin oxide thin films (SnO2, SnO2:Ru) with different thicknesses, in a controlled atmosphere of propane gas (C3H8) at different operation temperatures. The films were deposited onto soda-lime glass substrates by the spray pyrolysis technique at different deposition temperatures, namely, 300, 350, 400, and 450°C. All the films were annealed in vacuum at 400°C during 1 h in order to stabilize the surface physical characteristics. The sensing properties of the films were characterized by the surface electrical resistance ratio in a C3H8 atmosphere, and air as reference. Maximum sensitivities, on the order of 1.4 and 7.4 were obtained for undoped SnO2, and, SnO2:Ru thin films, respectively.